(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The socio-economic development of any country is based on natural resources. The natural resources are essential to the economy of the nation since they play a critical role in the provision of employment, they are a source of raw materials for various industries, act as the source of food and income, medicine as well as energy. Due to increase in population, these resources are over stretched often leading to resource depletion. Ultimately the depletion of natural resources has led to increase in the cost of living ,changes in weather pattern and decline in economic , social and cultural benefits that were accrued as a result of their utilisation .It is essential for nations to learn how to use these resources in sustainable manner to ensure that benefits are enjoyed in present as well as future generations There is need to prudently manage these delicate resources with the current trend in the advancement in the field of information technology, natural resources managers have now laid a lot of emphasis on the use of remote sensing and GIS technology in the management of natural resources,. These technologies provide a platform through which managers can generate informative data and the information that can be used to make sound decisions for sustainable development. This study is based on secondary data and information which includes research papers, reports, workshop outputs and information published in the websites of the related organizations .Thus, this paper presents an overview of the GIS and Remote Sensing applications in natural resources management and sustainable development.